Chemical composition and swelling of normal and osteoarthrotic femoral head cartilage. I. Chemical composition. - Venn, M (1977)
Radiochemical and biochemical methods were used to characterize post-mortem and osteoarthrotic femoral head cartilage. Fixed charge density measurements were correlated with glycosaminoglycan content as estimated by uronic acid and hexosamine analyses. In post-mortem cartilage water content decreased from a maximum at the surface to a minimum in the deep zones. In the osteoarthrotic specimens water content was greatest in the middle zones. Glycosaminoglycan content increased with depth and in the osteoarthrotic specimens was reduced throughout the depth of the cartilage. With increasing degeneration there was an increase in water content and decrease in glycosaminoglycan content. The difference in the water content profile in osteoarthrotic cartilage was explained in terms of damage to the collagen network. In osteoarthrosis the latter is no longer capable of restraining the swelling pressure produced by the glycosaminoglycans and swelling is greatest in the midzones, where glycosaminoglycan content is highest.